Identification of Lead Contamination in the Food Chain and Environment Surrounding Breastfeeding Mothers in Highland Agricultural Areas - Pangestuti, Dina Rahayuning; Kartini, Apoina; Suhartono, Suhartono; Lisnawati, Naintina; Putranto, Thomas Triadi; Susanto, Novie (Universitas Airlangga, 2025)
Introduction: Lead in the environment can be more easily absorbed by individuals with nutritional deficiencies, particularly breastfeeding mothers residing in agricultural areas near lead sources. Contaminated breast milk can disrupt infants' growth and development. This study aims to identify lead contaminants in the environment and assess the nutritional status of breastfeeding mothers to provide preventive measures. Methods: This cross-sectional study was conducted in the highland agricultural area of Semarang Regency in October 2021. Environmental samples, including air from agricultural land, settlements, groundwater, and raw food were carried out as environmental samples from 31 breastfeeding mothers. Dietary intake, haemoglobin, MCV, MCH, MCHC, and lead levels in breast milk was carried out. Lead content was analysed using ICP-OES. Geographic information system (GIS) was used to compare spatial distribution lead status levels with identified exposure factors. Results and Discussion: Median age of breastfeeding mothers was 24 years, with 72% being housewives, having a senior high school education. Median age of the infants was 2.5 months, 32% being boys, and 48% were exclusively breastfed. Mean hemoglobin level of the mothers was 13 ± 1.4 g/dL (13.8% was anemic) and median lead level in breast milk was 0.019 ppm. None of the mothers met their recommended macro- and micronutrient intake. Lead content in foods was 0.02-0.180 ppm, groundwater 0.017-0.034 ppm, and air 0-1.56 μg/Nm3 over a three-hours. Conclusion: The environment surrounding breastfeeding mothers contains lead, particularly in the air, and these mother experiences nutritional deficiencies, thereby increasing the risk of lead absorption.